Mantle plumes and their effects - Choudhuri, Mainak (SpringerBriefs in earth system sciences., 2016)
This book presents a brief synopsis of the current academic understanding of the plume hypothesis, its surface manifestations and shortcomings. It describes methods for estimating the uplift history of a region due to plume activity. Different models for the elastic properties of the lithosphere and its estimation as a background for plume emplacement are discussed, the plume hypothesis is introduced and the major plume types and their effect on the lithosphere are described. Two chapters are dedicated to the dynamic and permanent topography produced by an impinging plume head below the lithosphere and its estimation. The historical background of the plume hypothesis, its criticisms and alternatives are presented.